Irrigation periods, broomrape control treatments and the growth performance of pea (Pisum sativum) - DAWOOD, EMAN M; A, ZEIN A; SOLIMAN, I E; HAMZA, AMANY M; SHARSHAR, A A H (The Indian Journal of Agricultural Sciences, 2019)
Pea (Pisum sativum L.) is one of the most important vegetable crops but it is threatened by the holoparasitic plant broomrape (Orobanche crenata Forsk). Therefore, two field experiments were conducted in Sakha Agriculture Research Station, Egypt, during 2015–16 and 2016–17 to evaluate the effect of interaction between irrigation periods, and broomrape control treatments to control broomrape, yield and its components in pea and glyphosate residues in pea seeds. The results illustrated that irrigation period after 14 days followed by 21 days decreased broomrape growth and gave rise to the highest values for pea yield and its components. All broomrape control treatments significantly decreased broomrape growth and significantly increased yield and its components. No residues of herbicide (glyphosate at 6.35 g a.i./ha) were detected in pea seeds at harvest. These results indicated that in heavily infested soil with broomrape, irrigation should be done at 14 days interval and glyphosate should be sprayed twice. This gave best broomrape control and increased pea seed yield (t/ha), without any residues in pea seeds at harvest.